Attuned to Loss: Rhetoric of Solastalgia in Richard Powers’ "Bewilderment" and Emmi Itäranta’s "The Moonday Letters" - Musteikytė, Radvilė (Finnish Society for Science Fiction and Fantasy Research, 2025)
This article analyzes two contemporary novels that reflect on the devastation of the Earth: Bewildermentby American author Richard Powers (2021) and The Moonday Letters(2020) by Finnish author Emmi Itäranta, arguing that both novels invite readers to engage with solastalgia –a distress caused by witnessing environmental changes. The evocation of solastalgia (as an environmentally-attuning readerly affect) is discussed by employing James Phelan’s rhetorical theory of narrative, particularly his and Matthew Clark’s model of three narrative components. Accounting for both content and form, the threefold analysis touches on the many similarities of the seemingly different novels: their Earth-centeredness, the theme of loss and how it is rescaled from personal to environmental, as well as storyworld-internal worldbuilding that repeatedly interrupts the progression of narratives. This reading contributes to discussions about the functioningand functionsof fiction in the Anthropocene.